Radionuclides deposition over Antarctica - Pourchet, Michel; Magand, Olivier; Frezzotti, Massimo; Ekaykin, Alexey A.; Winther, Jan Gunnar (Journal of Environmental Radioactivity, 2003)
A detailed and comprehensive map of the distribution patterns for both natural and artificial radionuclides over Antarctica has been established. This work integrates the results of several decades of international programs focusing on the analysis of natural and artificial radionuclides in snow and ice cores from this polar region. The mean value (37±20 Bq m−2) of 241Pu total deposition over 28 stations is determined from the gamma emissions of its daughter 241Am, presenting a long half-life (432.7 yrs). Detailed profiles and distributions of 241Pu in ice cores make it possible to clearly distinguish between the atmospheric thermonuclear tests of the fifties and sixties. Strong relationships are also found between radionuclide data (137Cs with respect to 241Pu and 210Pb with respect to 137Cs), make it possible to estimate the total deposition or natural fluxes of these radionuclides. Total deposition of 137Cs over Antarctica is estimated at 760 TBq, based on results from the 90–180° East sector. Given the irregular distribution of sampling sites, more ice cores and snow samples must be analyzed in other sectors of Antarctica to check the validity of this figure.
Keywords: Antarktis; geofysikk; geologi; glasiologi; radioaktivitet

Antarktis, i fare for forurensing, som mulig dumpeplass for radioaktivt kjernefysisk avfall - Lund, Thoralv (Polarposten, 1973)
Keywords: Antarktis; miljøvern; radioaktivitet